Changes in reasons for visits to primary care after the start of the COVID-19 pandemic: an international comparative study by the International Consortium of Primary Care Big Data Researchers (INTRePID) - Tu, Karen (2024)
Background: The COVID-19 pandemic has reshaped healthcare delivery worldwide. Objective: To explore potential changes in the reasons for visits and modality of care in primary care settings through the International Consortium of Primary Care Big Data Researchers (INTRePID). Methods: We conducted a cross-sectional, retrospective study from 2018–2021. We examined visit volume, modality, and reasons for visits to primary care in Argentina, Australia, Canada, China, Peru, Norway, Singapore, Sweden, and the USA. The analysis involved a comparison between the pre-pandemic and pandemic periods. Results: There were more than 215 million visits from over 38 million patients during the study period in INTRePID primary care settings. Most INTRePID countries experienced a decline in monthly visit rates during the first year of the pandemic, with rate ratios (RR) and 95% confidence intervals (CI) ranging from RR:0.57 (95%CI:0.49–0.66) to RR:0.90 (95%CI:0.83–0.98), except for in Canada (RR:0.99, 95%CI:0.94–1.05) and Norway (RR:1.00, 95% CI:0.92–1.10), where rates remained stable and in Australia where rates increased (RR:1.19, 95%CI:1.11–1.28). Argentina, China, and Singapore had limited or no adoption of virtual care, whereas the remaining INTRePID countries varied in the extent of virtual care utilization. In Peru, virtual visits accounted for 7.34% (95%CI:7.33%-7.35%) of all interactions in the initial year of the pandemic, dipping to 5.22% (95%CI:5.21%-5.23%) in the subsequent year. However, in Canada 75.30% (95%CI:75.20%-75.40%) of the visits in the first year were virtual, decreasing to 62.77% (95%CI:62.66%-62.88%) in the second year. Diabetes, hypertension and/or hyperlipidemia and general health exams were in the top 10 reasons for visits in 2019 for all countries. Anxiety, depression and/or other mental health related reasons were among the top 10 reasons for virtual visits in all countries that had virtual care. Conclusions: The pandemic resulted in changes in reasons for visits to primary care, with virtual care mitigating visit volume disruptions in many countries.